ASPEK HUKUM PERLINDUNGAN TERHADAP ANAK PELAKU TINDAK PIDANA YANG DIJATUHI SANKSI PIDANA - Antoni Simanjuntak; Nurmala Waty; Marlina Marlina (Jurnal Mahupiki, 2017)
ABSTRAKSIAnthoni Agung Pratama Simanjuntak¹Nurmalawaty²Marlina³Children are a part of the youth of a nation that has the potential to advance the nation if it had grown.  In Indonesia real situation of children is very alarming. Evidenced by the many children who commit criminal acts. The sanctions measures adopted against children committed a crime, it is more focused on the welfare of the child rather than the interests o f society as a whole. Thus the punishment meant as retaliation dideritakan to a child. The impact of imposition of penalties on child will greatly affect a child's behavior and or physical, mental child that would impose itself as the future generation.The method used in this thesis is the study yuridisnormatif with the approach used is the approach of legislation relating to child protection, juvenile justice system in Indonesia. The material was taken from the writing of primary legal materials, secondary law, and tertiary legal materials.Based on this research can disimpulkanpenjatuhan criminal sanctions against children perpetrators of criminal acts according to Law No. 23 of 2002 Juncto Act No. 35 of 2014adalah requires states particularly on special  protection for children in conflict with the law are implemented through treatment humanly appropriate rights children, providing officers escort a special early on, providing facilities specifically, the application of sanctions appropriate to the best interests of the child, monitoring and recording constantly on the development of children in conflict with the law, guarantee to maintain relationships with their parents or relatives and protection from mass media overload and labeling in society. In Law No. 11 year 2012 has also been set up measures to protect children during the trial, among others the protection of children's rights under investigation, arrest or detention, and prosecution to prevent children perpetrator of that offense of inhuman treatment and protecting children and their rights in order to grow and develop optimally without violence and discrimination.